2020
DOI: 10.1136/bmjopen-2020-041339
|View full text |Cite
|
Sign up to set email alerts
|

Women’s experiences and expectations after disclosure of intimate partner abuse to a healthcare provider: A qualitative meta-synthesis

Abstract: ObjectiveTo identify and synthesise the experiences and expectations of women victim/survivors of intimate partner abuse (IPA) following disclosure to a healthcare provider (HCP).MethodsThe databases MEDLINE, Embase, CINAHL, PsychINFO, SocINDEX, ASSIA and the Cochrane Library were searched in February 2020. Included studies needed to focus on women’s experiences with and expectations of HCPs after disclosure of IPA. We considered primary studies using qualitative methods for both data collection and analysis p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
57
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 65 publications
8
57
1
Order By: Relevance
“…They suggested that, rather than seeking to take control, HCPs could “lessen their discomfort if they recognize that their role is as validator, listener, and advisor” (p.772). This certainly resonates with the findings of our recent meta-synthesis of women’s expectations of HCPs in the context of IPA [ 17 ]. We found that women wanted HCPs to facilitate choice and control in their interactions, and to provide advocacy and action that was guided by the woman’s individual needs and wishes [ 17 ].…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…They suggested that, rather than seeking to take control, HCPs could “lessen their discomfort if they recognize that their role is as validator, listener, and advisor” (p.772). This certainly resonates with the findings of our recent meta-synthesis of women’s expectations of HCPs in the context of IPA [ 17 ]. We found that women wanted HCPs to facilitate choice and control in their interactions, and to provide advocacy and action that was guided by the woman’s individual needs and wishes [ 17 ].…”
Section: Discussionsupporting
confidence: 88%
“…This certainly resonates with the findings of our recent meta-synthesis of women’s expectations of HCPs in the context of IPA [ 17 ]. We found that women wanted HCPs to facilitate choice and control in their interactions, and to provide advocacy and action that was guided by the woman’s individual needs and wishes [ 17 ]. Hegarty and McKibbin’s review [ 21 ] similarly identifies that adopting an advocacy approach rather than a controlling one is central to practitioner readiness to address IPA.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations